2014
DOI: 10.1155/2014/401760
|View full text |Cite
|
Sign up to set email alerts
|

Does Pulsed Magnetic Field Therapy Influence Nerve Regeneration in the Median Nerve Model of the Rat?

Abstract: The aim of this study was to evaluate the impact of pulsed magnetic field therapy on peripheral nerve regeneration after median nerve injury and primary coaptation in the rat. Both median nerves were surgically exposed and denervated in 24 female Wistar rats. A microsurgical coaptation was performed on the right side, whereas on the left side a spontaneous healing was prevented. The study group underwent a daily pulsed magnetic field therapy; the other group served as a control group. The grasping force was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Reperfusion may occur and the subsequent decrease in pressure on nerve tissue leads to the high-pressure redeposition of oxygen and nutrients and the increased formation of free radicals, which leads to lipid peroxidation (LPO) and tissue damage ( 3 ). The cumulative impact of ischemic and mechanical processes in this type of nerve damage may be more pronounced than their individual effects ( 3 , 6 , 7 ). Although peripheral nerves are capable of undergoing regeneration following injury, this process and the post-traumatic results are typically slow and weak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reperfusion may occur and the subsequent decrease in pressure on nerve tissue leads to the high-pressure redeposition of oxygen and nutrients and the increased formation of free radicals, which leads to lipid peroxidation (LPO) and tissue damage ( 3 ). The cumulative impact of ischemic and mechanical processes in this type of nerve damage may be more pronounced than their individual effects ( 3 , 6 , 7 ). Although peripheral nerves are capable of undergoing regeneration following injury, this process and the post-traumatic results are typically slow and weak.…”
Section: Introductionmentioning
confidence: 99%
“…Although peripheral nerves are capable of undergoing regeneration following injury, this process and the post-traumatic results are typically slow and weak. Peripheral nerve trauma is therefore a significant cause of morbidity ( 6 ). A large amount of research has been conducted aiming to reduce the effects of peripheral nerve damage; however, to the best of our knowledge, no effective therapeutic strategies have been identified ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches to repair injured peripheral nerve are thus required. Various forms of external physical stimulation (electric stimulation, laser stimulation, ultrasound, magnetic field, and so on) can enhance the functional recovery of injured peripheral nerve (Mendonça et al 2003;Shen et al 2013;Kim et al 2013;Beck-Broichsitter et al 2014). Mendonça et al (2003) found that low intensity, directly applied electric stimulation (1 lA) enhanced both morphologic and functional regeneration of rat crushed sciatic nerve.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that low-level laser stimulation could improve motor function, enhance electrophysiological reaction, reduce muscle atrophy, and promote histomorphometric recovery. In addition, pulsed magnetic field therapy also has a positive influence on the functional regeneration of rat after a median nerve injury (Beck-Broichsitter et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Re-growth of peripheral nerve fibers could be induced using different approaches. Historically, enhanced nerve regeneration has been promoted by the administration of drugs [ 1 ], physical factors (magnetic field) [ 2 , 3 ], and electrical stimulation [ 4 - 6 ]. Nerve surgery [ 7 ] and the microsurgical suture technique [ 8 ] have witnessed impressive development in recent years.…”
Section: Introductionmentioning
confidence: 99%